2018
DOI: 10.1177/2051570718791785
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive acceptance mechanisms of discontinuous food innovations: The case of insects in France

Abstract: In a context of changing food consumption patterns, discontinuous innovations are a major challenge for the food industry. This article aims to identify the cognitive processes underpinning the acceptance of discontinuous food innovations through the study of classification and encoding mechanisms of mental categorisation. A qualitative study applied to entomophagy explores these mechanisms according to the extent of product processing and their consequences on acceptance by consumers. These results enrich Beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…Focus groups as a method is often used when the aim is to explore attitudes, ideas and thoughts among consumers and different populations segments (see, e.g., Atik & Ozdamar Ertekin, 2013). Previous studies have also used focus groups in investigating consumer perceptions and acceptance of eating insects (Gallen, Pantin‐Sohir, & Peyrat‐Guillard, 2019; Stull et al., 2018; Tan et al., 2015). The preschool in the study included children from 1–5 years of age and was divided into one section with children who were 1–2 years old and one with children 3–5 years old.…”
Section: Methodsmentioning
confidence: 99%
“…Focus groups as a method is often used when the aim is to explore attitudes, ideas and thoughts among consumers and different populations segments (see, e.g., Atik & Ozdamar Ertekin, 2013). Previous studies have also used focus groups in investigating consumer perceptions and acceptance of eating insects (Gallen, Pantin‐Sohir, & Peyrat‐Guillard, 2019; Stull et al., 2018; Tan et al., 2015). The preschool in the study included children from 1–5 years of age and was divided into one section with children who were 1–2 years old and one with children 3–5 years old.…”
Section: Methodsmentioning
confidence: 99%
“…. Gierts et al, 2016;Gallen, Gaelle, & Peyrat-Guillard, 2018;Verbeke, 2015). Fear of eating insects is well established in Western countries and may be due to anticipated negative postingestion consequences or from the knowledge of the animals' habitats (Caparros Caparros Megido, Gierts et al, 2016;Verbeke, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages of edible insects, their acceptance in Western countries is still quite low (Osimani et al., ). Consumers’ fear of eating insects has been identified as one of the most important factors related to determining edible insect acceptance (Caparros Megido, Alabi et al., ; Caparros Megido, Gierts et al., ; Gallen, Gaelle, & Peyrat‐Guillard, ; Verbeke, ). Fear of eating insects is well established in Western countries and may be due to anticipated negative postingestion consequences or from the knowledge of the animals’ habitats (Caparros Megido, Alabi et al., ; Caparros Megido, Gierts et al., ; Verbeke, ).…”
Section: Introductionmentioning
confidence: 99%
“…This was probably partly due to the direct influence of co-creators who were not lead users (Bilgram et al, 2008) and probably less innovative. Another explanation could be the need to reduce the risk of rejection for products based on spirulina, which is, like insects, a discontinuous ingredient (Gallen et al, 2018). These can explain why Rudder (2003) observed that manufacturers make "adjustments" more often than "new-to-the-world innovations".…”
Section: Performance Of Productsmentioning
confidence: 99%